(3cJGH GdTGed aj GdCOhjI GdeaQOIs - (3jhSa Hf YHO Gddg Hf Ydj GdJfhNj, SHW CHj Ydj efUhQ Hf CHj GdaVd GdUhQjs
(3ChdgG (B:s
(3bGd CeG HYO GdMeO ddg GdPi CNQL GdMH hCfTGA GdMH ceG CfRd GdOhGA hGdge GdWH aSHMGfg ef QH HOC GdUfYI s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg (B: (3hEPG CNP ef QDhS NeSI hObJ ObkG fGYekG hSNfJ ai bThQ QeGf eY Ogf hQO hbWQ s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs